Design optimization and experimental study of coaxial powder-feeding nozzle in the laser cladding process. (January 2019) - Ju, H; Zhang, Z J; Lin, C X; Liu, Z J; Jiang, H L
Abstract: To improve the powder convergence and cladding layer quality, the three-dimensional axisymmetrical powder flow through a coaxial feeding nozzle was simulated by the Eulerian-Eulerian two-fluid model. With the composite design via the response surface method, the significance between the main geometric dimensions of nozzle and fluidization characteristics of powder flow was analyzed and regression-fitted. Moreover, a mathematical model was constructed to optimize the nozzle structure, and the optimal nozzle was used in laser cladding experiments. The results show that appropriate powder flow can be obtained in the condition of the carrier gas more than 9 l/min, and the powder sending rate less than 7.5 g/min. The structural parameters of the optimized nozzle are as follows: nozzle angle of 62.94°, outlet width of 1.0mm, exit radius of 5.83mm, and flow separation angle of 3.00°. With the optimized nozzle, the waist diameter and focus depth of the original powder flow decreased by 39.4 and 46.4%, respectively, and the discrepancy between the experimental and simulation results was less than 9%. With the appropriate technological parameters, a layer with good geometry morphology and appropriate dilution rate can be prepared in the laser cladding process with a coaxial feeding nozzle.